“Crawling Takes Away My Dignity”: Effects of Inaccessible Environments on Persons with Mobility Disabilities in Ghana - Naami, Augustina (Southern African Journal of Social Work and Social Development, 2022)
Individuals with disabilities in Ghana continue to face barriers in the built environment, transportation, information and social spheres, despite local and international laws that promote their human rights and freedoms. These barriers have a negative impact on the education, employment, healthcare, safety, security and social life of persons with disabilities. Little attention is given to the way in which these barriers affect the dignity and self-determination of persons with mobility disabilities. Guided by the social relational model of disability and photovoice methodology, in this study, I sought to fill the gap. I used purposive and snowball sampling to recruit 10 persons with mobility disabilities who engaged in the data collection and analysis. The study outcome indicates that the dignity of persons with mobility disabilities was compromised while managing inaccessible environments requiring them to crawl, be carried, and rely on others for help. The findings indicate that self-determination was an issue for the participants because they either did not have opportunities or had limited opportunities to choose independently because of the restrictions posed by the environment. Education, religious and economic institutions and all other service providers should ensure that their environments are accessible and safer for persons with mobility disabilities. The government should ensure the enforcement of disability-related policies to promote accessibility for persons with disabilities. An accessible environment could promote the dignity, self-determination, health and overall well-being of persons with mobility disabilities.